All-solid-state battery and method for manufacturing the same

By adding adhesives to the electrode layer and solid electrolyte layer of the all -solid battery, and controlling the suppression temperature during the suppression process, the electrode plate warration is solved, the sealing strength of the seal layer is ensured, and the mechanical strength of the battery is improved.

CN113196545BActive Publication Date: 2025-01-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980074253.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-04
Publication Date
2025-01-28
Estimated Expiration
2039-12-04

AI Technical Summary

Technical Problem

The existing all-solid batteries are prone to warping of the electrode plate during the pressing process, resulting in a decrease in the sealing strength of the sealing layer, which in turn affects the mechanical strength of the battery.

Method used

By adding adhesives in the electrode layer and solid electrolyte layer, and the suppression temperature sets the glass transformation temperature higher than the adhesive during the suppression process, but lower than the glassized transformation temperature of the sealing material to suppress the electrode plate The warning strength of the sealing layer is maintained.

Benefits of technology

Effectively inhibit the warning of the electrode board, ensure the sealing strength of the seal layer, and improve the mechanical strength of the all -solid battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113196545B_ABST
    Figure CN113196545B_ABST
Patent Text Reader

Abstract

A technical solution disclosed herein involves an all-solid-state battery comprising: an electrode layer; a solid electrolyte layer containing a solid electrolyte; and a sealing layer containing a sealing material, wherein at least one of the electrode layer and the solid electrolyte layer contains an adhesive, and the glass transition temperature of the sealing material is higher than the glass transition temperature of the adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an all-solid-state battery and a method for manufacturing the all-solid-state battery. Background Art

[0002] Patent Documents 1 and 2 describe all-solid-state batteries including a sealing layer in contact with a battery element.

[0003] Prior Art Literature

[0004] Patent Document 1: Japanese Patent Application Publication No. 2017-73374

[0005] Patent Document 2: Japanese Patent Application Publication No. 2012-38425 Summary of the invention

[0006] Batteries using solid electrolytes are sometimes provided with a sealing layer for the purpose of suppressing the intrusion of moisture into the battery or maintaining the structure or preventing short circuits caused by contact between current collectors.

[0007] In the prior art, it is desired to ensure the mechanical strength of a battery having a sealing layer. In order to ensure the mechanical strength of a battery, it is important to sufficiently ensure the sealing strength provided by the sealing layer.

[0008] This disclosure has:

[0009] Electrode layer;

[0010] a solid electrolyte layer comprising a solid electrolyte; and

[0011] A sealing layer comprising a sealing material,

[0012] At least one selected from the electrode layer and the solid electrolyte layer includes a binder, and the sealing material has a glass transition temperature higher than a glass transition temperature of the binder.

[0013] According to the present disclosure, it is possible to sufficiently ensure the sealing strength by the sealing layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1A This is a schematic cross-sectional view of a battery according to one embodiment of the present disclosure.

[0015] Figure 1B It is a schematic cross-sectional view of a battery according to a modification.

[0016] Figure 2 This is a flowchart showing an example of a method for manufacturing a battery.

[0017] Figure 3 This is a test photo of sample 1.

[0018] Figure 4This is a test photo of sample 2. DETAILED DESCRIPTION

[0019] (Insights that form the basis of this disclosure)

[0020] From the perspective of large-area, continuous production and mass production of batteries, the application of the coating process to the manufacture of all-solid-state batteries has been studied. In the coating process, a slurry is prepared by dispersing raw material powder in a solvent. The slurry is applied to the collector by a coating method such as screen printing and die coating to form a coating film. The solvent is volatilized from the coating film by a thermal process such as a drying furnace. Thus, an electrode plate having a collector and an electrode layer is obtained. Usually, a binder is added to the slurry in order to impart viscosity suitable for the coating process or to increase the strength of the electrode layer.

[0021] As an adhesive, a thermoplastic resin is often used. Some thermoplastic resins have a glass transition temperature. When a predetermined load is applied, the thermoplastic resin exhibits plastic deformation behavior at a temperature higher than the glass transition temperature, and exhibits elastic deformation behavior at a temperature lower than the glass transition temperature.

[0022] A slurry containing a solid electrolyte is applied to an electrode plate to form a coating. The coating is dried to form a solid electrolyte layer on the electrode plate. The electrode plate as the positive electrode is placed opposite to the electrode plate as the negative electrode and pressed to obtain a fully solid battery. In order to improve battery performance, the electrode plate is sometimes pressed before applying the slurry containing a solid electrolyte.

[0023] The inventors of the present invention have conducted careful research and learned for the first time that the electrode plate warps when the pressing temperature is lower than the glass transition temperature of the binder contained in at least one layer selected from the electrode layer and the solid electrolyte layer. It is believed that the warping occurs due to the following reasons. During the period when the pressing pressure is applied and maintained, the particles constituting the electrode layer (mainly active materials and solid electrolytes) move slightly in a manner of filling each other's gaps. This increases the filling rate of the electrode layer. After a certain filling rate is achieved by a predetermined pressing pressure, the extension of the electrode layer is mainly limited to a direction orthogonal to the pressing direction. In other words, the electrode layer stretches in a direction orthogonal to the pressing direction, so tensile stress is generated in the electrode layer. On the other hand, compressive stress is generated in the collector in contact with the electrode layer. When the pressing temperature is lower than the glass transition temperature of the binder, when the load during pressing is removed, the binder contained in the electrode layer shows elastic deformation behavior, so the binder will restore its original shape and original position. As a result, the electrode plate warps due to the tensile stress of the electrode layer and the compressive stress of the collector. The positive electrode and the negative electrode are warped in a manner that the positive electrode and the negative electrode are close in the center of the battery and are away from each other in the periphery of the battery. At the periphery of the battery, the electrode plate is warped in the direction in which the collector is away from the sealing layer. As a result, the sealing strength brought by the sealing layer is reduced. In this way, in the previous all-solid-state battery with a sealing layer, there is a problem of the electrode layer peeling off from the collector or the sealing strength brought by the sealing layer being insufficient.

[0024] (Summary of a technical solution involved in the present disclosure)

[0025] A first aspect of the present disclosure relates to a battery comprising:

[0026] Electrode layer;

[0027] a solid electrolyte layer comprising a solid electrolyte; and

[0028] A sealing layer comprising a sealing material,

[0029] At least one selected from the electrode layer and the solid electrolyte layer includes a binder, and the sealing material has a glass transition temperature higher than a glass transition temperature of the binder.

[0030] According to the first aspect, it is possible to provide a battery in which the sealing strength provided by the sealing layer is sufficiently ensured.

[0031] In the second technical solution of the present disclosure, for example, based on the battery involved in the first technical solution, the electrode layer and the solid electrolyte layer can be stacked on each other, and the sealing layer can be in contact with at least one selected from the side surface of the electrode layer and the side surface of the solid electrolyte layer. According to such a structure, the sealing strength brought by the sealing layer can be more fully ensured.

[0032] In the third technical solution of the present disclosure, for example, on the basis of the battery involved in the first or second technical solution, the binder may contain a thermoplastic resin. The thermoplastic resin is softened by heating to a temperature above the glass transition temperature and pressing. Therefore, if the binder contains a thermoplastic resin, the filling rate of the electrode layer and / or the solid electrolyte layer is improved. In addition, by softening the binder, the electrode layer and / or the solid electrolyte layer can be easily molded, so the pressing time can be shortened.

[0033] In the fourth technical solution of the present disclosure, for example, in the battery according to the third technical solution, the thermoplastic resin may include at least one selected from styrene-butadiene copolymer and styrene-ethylene-butadiene copolymer. When these copolymers are used as binders, they exhibit good solubility even in solvents with low polarity.

[0034] In a fifth aspect of the present disclosure, for example, in the battery according to any one of the first to fourth aspects, the glass transition temperature of the binder may be lower than 120° C. In this temperature range, the glass transition temperature of the binder is lower than the pressing temperature, thereby suppressing warping of the electrode plate.

[0035] In the sixth technical solution of the present disclosure, for example, in the battery according to any one of the first to fifth technical solutions, the glass transition temperature of the sealing material may be 120° C. or higher. In this temperature range, the glass transition temperature of the sealing material is higher than the glass transition temperature of the adhesive, so the sealing strength provided by the sealing layer can be maintained.

[0036] In a seventh aspect of the present disclosure, for example, in the battery according to any one of the first to sixth aspects, the sealing material may include polyimide. By including a thermoplastic resin having a high glass transition temperature such as polyimide, the sealing strength of the sealing layer can be maintained even at a high pressing temperature.

[0037] In the eighth aspect of the present disclosure, for example, in the battery according to any one of the first to seventh aspects, the electrode layer may include the electrode active material and the solid electrolyte. By including the electrode active material and the solid electrolyte, an efficient electrode layer can be produced.

[0038] A ninth technical solution of the present disclosure relates to a method for manufacturing a battery, comprising:

[0039] heating at least one selected from the electrode layer and the solid electrolyte layer to a pressing temperature; and

[0040] pressing at least one selected from the electrode layer and the solid electrolyte layer at the pressing temperature,

[0041] One or both of the electrode layer and the solid electrolyte layer to be pressed at the pressing temperature contains a binder,

[0042] The pressing temperature is above the glass transition temperature of the binder.

[0043] According to the ninth aspect, the battery of the present disclosure can be efficiently manufactured.

[0044] In the 10th technical solution of the present disclosure, for example, on the basis of the manufacturing method of the battery involved in the 9th technical solution, it may also include forming a sealing layer in a manner of contacting at least one selected from the electrode layer and the solid electrolyte layer, and the sealing layer may be heated to the pressing temperature when at least one selected from the electrode layer and the solid electrolyte layer is heated to the pressing temperature, and the sealing layer may be pressed at the pressing temperature when at least one selected from the electrode layer and the solid electrolyte layer is pressed. By providing a sealing layer, the mechanical strength of the battery can be ensured. In addition, by pressing the sealing material at the pressing temperature, the sealing strength brought by the sealing layer can be maintained.

[0045] In the 11th technical solution of the present disclosure, for example, based on the manufacturing method of the battery involved in the 10th technical solution, the glass transition temperature of the sealing material constituting the sealing layer can be higher than the glass transition temperature of the adhesive. When the glass transition temperature of the sealing material is higher than the glass transition temperature of the adhesive, the sealing strength brought by the sealing layer can be maintained, and thus the mechanical strength of the all-solid battery can be maintained.

[0046] In the 12th technical solution of the present disclosure, for example, on the basis of the manufacturing method of the battery involved in the 11th technical solution, the glass transition temperature of the sealing material constituting the sealing layer can be higher than the pressing temperature. When the glass transition temperature of the sealing material is higher than the pressing temperature, the sealing material does not undergo plastic deformation. As a result, the sealing strength brought by the sealing layer can be maintained, so the mechanical strength of the all-solid battery can be maintained.

[0047] (Implementation Method)

[0048] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings, but the present disclosure is not limited to the following embodiments.

[0049] [Structure of all-solid-state batteries]

[0050] Figure 1A 1 is a schematic cross-sectional view of an all-solid-state battery 10 according to an embodiment. Figure 1A As shown, the all-solid battery 10 includes a positive electrode 11, a negative electrode 12, a solid electrolyte layer 5 and a sealing layer 8. The positive electrode 11 has a positive electrode collector 3 and a positive electrode layer 4. The negative electrode 12 has a negative electrode collector 6 and a negative electrode layer 7. The positive electrode layer 4 is arranged on the positive electrode collector 3. The negative electrode layer 7 is arranged on the negative electrode collector 6. The solid electrolyte layer 5 is arranged between the positive electrode layer 4 and the negative electrode layer 7. The solid electrolyte layer 5 is in contact with the positive electrode layer 4 and the negative electrode layer 7, respectively. The sealing layer 8 is in contact with the positive electrode collector 3 and the negative electrode collector 6. The positive electrode layer 4 and the negative electrode layer 7 are examples of electrode layers, respectively. The positive electrode 11 and the negative electrode 12 are examples of electrode plates, respectively. The sealing layer 8 can inhibit the intrusion of moisture into the interior of the all-solid battery 10, or maintain the structure of the all-solid battery 10, and prevent short circuits caused by the contact between the positive electrode collector 3 and the negative electrode collector 6. As a result, the mechanical strength of the all-solid battery 10 can be ensured.

[0051] When the all-solid battery 10 is viewed from above, the sealing layer 8 has a frame shape. The positive electrode layer 4, the solid electrolyte layer 5 and the negative electrode layer 7 are surrounded by the sealing layer 8. The lower surface of the sealing layer 8 is in contact with the positive electrode collector 3, and the upper surface of the sealing layer 8 is in contact with the negative electrode collector 6.

[0052] In the present embodiment, the sealing layer 8 is in contact with the side 5t of the solid electrolyte layer 5. According to such a structure, the sealing strength brought by the sealing layer 8 can be more fully ensured. The sealing layer 8 is not in contact with the positive electrode layer 4 and the negative electrode layer 7. According to such a structure, in the manufacture of the all-solid battery 10, it is difficult for the sealing material to react with the electrode material. In other words, the risk of reduced battery performance can be avoided. In the manufacture of the all-solid battery, if the sealing material is impregnated in the electrode layer, the impregnated portion cannot function as an electrode. As a result, the performance of the battery is reduced. In the present embodiment, since the electrode layer is made before the sealing layer 8 is made, the above-mentioned problem is difficult to occur, and it is easy to define the area of ​​the electrode that contributes to power generation. In addition, even in the case of mass production of batteries, the performance of the battery is difficult to reduce.

[0053] Figure 1B 1 is a schematic cross-sectional view of a modified example of an all-solid battery 10B. In the modified example of the all-solid battery 10B, the side 4t of the positive electrode layer 4, the side 7t of the negative electrode layer 7, and the side 5t of the solid electrolyte layer 5 are in contact with the sealing layer 8. According to such a structure, the sealing strength brought by the sealing layer 8 can be fully ensured. In addition, the volume of the solid electrolyte layer 5 can be reduced, so it is possible to expect a reduction in the manufacturing cost of the all-solid battery 10B brought about by the reduction in material costs. The other structures of the all-solid battery 10B are the same as those of the all-solid battery 10.

[0054] Each structure of the all-solid-state battery 10 will be described in detail.

[0055] (positive electrode 11 and negative electrode 12)

[0056] The positive electrode 11 includes a positive electrode current collector 3 and a positive electrode layer 4 . The negative electrode 12 includes a negative electrode current collector 6 and a negative electrode layer 7 .

[0057] There is no particular limitation on the materials of the positive electrode collector 3 and the negative electrode collector 6, and the materials used in conventional lithium-ion batteries can be used. The material of the positive electrode collector 3 and the material of the negative electrode collector 6 can be the same or different. As the materials of the positive electrode collector 3 and the negative electrode collector 6, copper, copper alloy, aluminum, aluminum alloy, stainless steel, nickel, titanium, carbon, lithium, indium, and conductive resin can be cited. There is no particular limitation on the shape of the positive electrode collector 3 and the negative electrode collector 6. As the shape of the positive electrode collector 3 and the negative electrode collector 6, foil, film and sheet can be cited. The surfaces of the positive electrode collector 3 and the negative electrode collector 6 can be given concavoconvexity.

[0058] The electrode layer contains an active material. The composition of the active material is not particularly limited and can be selected according to the desired function. The electrode layer can contain other materials such as a conductive material, a solid electrolyte, and a binder as needed.

[0059] Active materials generally include positive electrode active materials and negative electrode active materials. The positive electrode active materials and negative electrode active materials are selected according to the required functions.

[0060] As positive electrode active materials, for example, transition metal oxides containing lithium, vanadium oxides, chromium oxides, and transition metal sulfides containing lithium can be cited. As transition metal oxides containing lithium, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNiCoMnO2, LiNiCoO2, LiCoMnO2, LiNiMnO2, LiNiCoMnO4, LiMnNiO4, LiMnCoO4, LiNiCoAlO2, LiNiPO4, LiCoPO4, LiMnPO4, LiFePO4, Li2NiSiO4, Li2CoSiO4, Li2MnSiO4, Li2FeSiO4, LiNiBO3, LiCoBO3, LiMnBO3, and LiFeBO3 can be cited. As examples of transition metal sulfides containing lithium, LiTiS2, Li2TiS3, and Li3NbS4 can be cited. One or more selected from these positive electrode active materials can be used.

[0061] Examples of negative electrode active materials include carbon materials, lithium alloys, metal oxides, lithium nitride (Li3N), metallic lithium, and metallic indium. Examples of carbon materials include artificial graphite, graphite, non-graphitizable carbon, and easily graphitizable carbon. Examples of lithium alloys include alloys of lithium and at least one metal selected from Al, Si, Pb, Sn, Zn, and Cd. Examples of metal oxides include LiFe2O3, WO2, MoO2, SiO, and CuO. A mixture or a composite of multiple materials may also be used as a negative electrode active material.

[0062] There is no particular limitation on the shape of the positive electrode active material and the negative electrode active material, for example, they are in the form of particles. There is no particular limitation on the size of the positive electrode active material and the negative electrode active material. When the positive electrode active material and the negative electrode active material are in the form of particles, the average particle size of the particles of the positive electrode active material and the average particle size of the particles of the negative electrode active material can be greater than 0.5 μm and less than 20 μm, or can be greater than 1 μm and less than 15 μm. The average particle size can be, for example, the median particle size (d50) measured using a particle size distribution measuring device.

[0063] In the case where the particle size distribution cannot be measured, the average particle size of the particles can be calculated by the following method. Use an electron microscope to observe the particle group, and calculate the area of ​​the specific particles in the electron microscope image by image processing. In the case where it is impossible to directly observe the particle group alone, use an electron microscope to observe the structure containing the particles, and calculate the area of ​​the specific particles in the electron microscope image by image processing. The diameter of a circle having an area equal to the calculated area is regarded as the diameter of the specific particle. Calculate the diameter of any number (for example, 10) of particles, and regard their average value as the average particle size of the particles.

[0064] There is no particular limitation on the conductive material, and it can be appropriately selected from the materials used in conventional lithium-ion batteries. As the conductive material, for example, graphite, carbon black, conductive fibers, conductive metal oxides and organic conductive materials can be cited. These conductive materials can be used alone or in combination of two or more.

[0065] There is no particular limitation on the solid electrolyte, and it can be appropriately selected from the materials used in conventional lithium-ion batteries according to the type of active material and the purpose of the all-solid battery 10. As solid electrolytes, for example, sulfide solid electrolyte materials, oxide solid electrolyte materials, other inorganic solid electrolyte materials, and organic solid electrolyte materials can be cited. The solid electrolyte can be used alone or in combination of two or more. There is no particular limitation on the shape of the solid electrolyte, for example, a particle shape can be cited. There is no particular limitation on the size of the solid electrolyte. When the solid electrolyte is in a particle shape, the average particle size of the particles of the solid electrolyte can be greater than 0.01 μm and less than 15 μm, or it can be greater than 0.2 μm and less than 10 μm. The average particle size can be, for example, the median particle size (d50) measured using a particle size distribution measuring device.

[0066] There is no particular limitation on the binder, and it can be appropriately selected from the materials usually used in lithium ion batteries. As a binder, for example, a thermoplastic resin can be mentioned. As a thermoplastic resin, thermoplastic elastomers such as styrene-butadiene copolymers and styrene-ethylene-butadiene copolymers can be mentioned. In the case of a slurry, in order to prevent the performance of the solid electrolyte such as ion conductivity from being reduced, a solvent with low polarity is sometimes used. Styrene-butadiene copolymers or styrene-ethylene-butadiene copolymers, when a slurry is prepared, show good solubility even for solvents with low polarity. Therefore, if these polymers are used, the performance of the solid electrolyte can be prevented from being reduced. Other examples of thermoplastic resins include ethyl cellulose, polyvinylidene fluoride, polyethylene, polypropylene, polyisobutylene, polystyrene, polyvinyl chloride, polyvinyl acetate, polymethyl methacrylate, polyethyl methacrylate, poly-n-propyl methacrylate, poly-n-butyl methacrylate, polydimethylsiloxane, cis-1,4-polybutadiene, polyisoprene, nylon-6, nylon-6,6, polyethylene terephthalate, polyvinyl alcohol, etc. These binders may be used alone or in combination of two or more.

[0067] The glass transition temperature of the adhesive is lower than the glass transition temperature of the sealing material described later. The glass transition temperature of the adhesive may be above 100°C, or may be above 120°C. When the glass transition temperature of the adhesive is lower than the glass transition temperature of the sealing material, the pressing temperature can be set between the glass transition temperature of the adhesive and the glass transition temperature of the sealing material. In other words, the pressing temperature is higher than the glass transition temperature of the adhesive and lower than the glass transition temperature of the sealing material. When the temperature difference is large enough, it is easy to set the pressing temperature to a temperature between the glass transition temperature of the adhesive and the glass transition temperature of the sealing material, so the pressing process can be easily implemented.

[0068] The glass transition temperature can be measured by thermomechanical analysis (TMA), dynamic viscoelasticity measurement (DMA), differential scanning calorimetry (DSC), differential scanning calorimeter thermal analysis (DTA), or the like.

[0069] (Solid electrolyte layer 5)

[0070] There is no particular limitation on the material of the solid electrolyte layer 5, and it can be appropriately selected from the materials used in conventional lithium-ion batteries according to the type of active material and the purpose of the all-solid battery 10. As the material of the solid electrolyte layer 5, for example, sulfide solid electrolyte materials, oxide solid electrolyte materials, other inorganic solid electrolyte materials, and organic solid electrolyte materials can be cited. The solid electrolyte can be used alone or in combination of two or more. There is no particular limitation on the shape of the solid electrolyte, for example, a particle shape can be cited. There is no particular limitation on the size of the solid electrolyte. When the solid electrolyte is in a particle shape, the average particle size of the particles of the solid electrolyte can be greater than 0.01 μm and less than 15 μm, or it can be greater than 0.2 μm and less than 10 μm. The average particle size can be, for example, the median particle size (d50) measured using a particle size distribution measuring device.

[0071] (Sealing layer 8)

[0072] As a sealing material constituting the sealing layer 8, a thermoplastic resin with a high glass transition temperature can be used. As a thermoplastic resin with a high glass transition temperature, for example, polyimide can be cited. By using polyimide, the sealing strength of the sealing layer 8 can be maintained even when the pressing temperature is high. That is, the range of the pressing temperature can be set on the high temperature side, so the all-solid battery 10 can be manufactured efficiently. In addition, the range of the glass transition temperature of the adhesive can also be set on the high temperature side, so more types of adhesives can be used. As other examples of thermoplastic resins that can be used as sealing materials, poly-α-methylstyrene, polycarbonate, polyacrylonitrile, etc. can be cited. In addition, thermosetting resins and photocurable resins can be used as sealing materials. They can be used alone or in combination of two or more. When the glass transition temperature of the sealing material is high enough, the sealing strength brought by the sealing layer can be fully maintained.

[0073] In order to strengthen the function of the sealing layer 8, the sealing material may include other materials such as functional powders and fibers. Other materials include inorganic fillers and silica gel. Inorganic fillers can strengthen the structural retention. Silica gel can strengthen water resistance. These functional powders or fibers can be used alone or in combination of two or more.

[0074] The glass transition temperature of the sealing material is higher than the glass transition temperature of the above-mentioned adhesive. The glass transition temperature of the sealing material may be above 120°C. The difference between the glass transition temperature of the sealing material and the glass transition temperature of the adhesive is, for example, above 10°C and below 60°C. In the case where the glass transition temperature of the sealing material is higher than the glass transition temperature of the adhesive, the pressing temperature can be set between the glass transition temperature of the sealing material and the glass transition temperature of the adhesive. In other words, the pressing temperature is higher than the glass transition temperature of the adhesive and lower than the glass transition temperature of the sealing material. When the temperature difference is large enough, it is easy to set the pressing temperature to a temperature between the glass transition temperature of the adhesive and the glass transition temperature of the sealing material, so the pressing process can be easily implemented.

[0075] [Method for manufacturing all-solid-state battery]

[0076] Next, an example of a method for manufacturing the all-solid-state battery 10 will be described. Figure 2 The procedure for manufacturing the all-solid-state battery 10 is shown.

[0077] First, in step S1, a positive electrode 11 and a negative electrode 12 are prepared. A mixture containing a positive electrode active material or a negative electrode active material and, as required, other materials such as a conductive material, a solid electrolyte, and a binder is prepared. The mixing ratio of each material is appropriately determined according to the intended use of the battery. Next, the mixture is mixed using a mixing device. There is no particular limitation on the mixing device, and a known device can be used. Examples of the mixing device include a planetary mixer and a ball mill. However, there is no particular limitation on the method for mixing the materials.

[0078] Then, the mixture containing the active material is attached to the current collector in a predetermined thickness, thereby obtaining an electrode plate having the current collector and the electrode layer.

[0079] Another method for preparing the electrode plate is as follows. First, a slurry is prepared by dispersing a mixture containing an active material in an appropriate solvent. The slurry is applied to the positive electrode collector 3 or the negative electrode collector 6 to form a coating film. The coating film is then dried to prepare the electrode plate. Examples of the slurry coating method include screen printing, die coating, spray coating, and scraper coating.

[0080] Next, in step S2, a solid electrolyte layer 5 is prepared. There is no particular limitation on the method for preparing the solid electrolyte layer 5, and a known method can be used. First, a mixture containing a solid electrolyte and a binder is prepared. The mixing ratio of each material is appropriately determined according to the intended use of the all-solid battery 10. Then, the mixture is mixed using a mixing device. There is no particular limitation on the mixing device, and a known device can be used. As the mixing device, a planetary mixer and a ball mill can be mentioned. However, there is no particular limitation on the method for mixing the materials.

[0081] A mixture containing a solid electrolyte is attached to the positive electrode layer 4 or the negative electrode layer 7 at a predetermined thickness. Thus, the solid electrolyte layer 5 is formed.

[0082] Another method for preparing the solid electrolyte layer 5 is as follows. First, a slurry is prepared by dispersing a mixture containing a solid electrolyte in an appropriate solvent. The slurry is applied to the positive electrode layer 4 or the negative electrode layer 7 to form a coating film. The coating film is then dried to prepare the solid electrolyte layer 5. Examples of the coating method of the slurry include screen printing, die coating, spray coating, and doctor blade methods.

[0083] Another method for producing the solid electrolyte layer 5 is as follows. The slurry is applied to a support material to form a coating. The coating is dried to obtain a solid electrolyte sheet. The solid electrolyte sheet is transferred from the support material to the positive electrode 11 or the negative electrode 12, thereby producing the solid electrolyte layer 5 arranged on the positive electrode 11 or the negative electrode 12.

[0084] The binder may be contained in at least one selected from the positive electrode layer 4, the negative electrode layer 7 and the solid electrolyte layer 5. The positive electrode layer 4, the negative electrode layer 7 and the solid electrolyte layer 5 may all contain a binder. The composition of the binder contained in the positive electrode layer 4 may be the same as or different from the composition of the binder contained in the solid electrolyte layer 5. The composition of the binder contained in the negative electrode layer 7 may be the same as or different from the composition of the binder contained in the solid electrolyte layer 5. The composition of the binder contained in the positive electrode layer 4 may be the same as or different from the composition of the binder contained in the negative electrode layer 7.

[0085] Next, in step S3, a sealing layer 8 is prepared. There is no particular limitation on the method for preparing the sealing layer 8, and a known method can be used. For example, the sealing material is applied to the electrode plate in a manner that contacts at least one selected from the electrode layer and the solid electrolyte layer 5. The sealing material may contact at least one selected from the positive electrode collector 3 and the negative electrode collector 6. As a coating method for the sealing material, screen printing, inkjet, coating using a dispenser, etc. can be cited. The sealing material is dried as needed to form a sealing layer 8.

[0086] Then, the positive electrode 11 and the negative electrode 12 are stacked to obtain an assembly of the positive electrode 11, the solid electrolyte layer 5, the negative electrode 12, and the sealing layer 8. The positive electrode layer 4 is arranged on the positive electrode collector 3, and the negative electrode layer 7 is arranged on the negative electrode collector 6. The solid electrolyte layer 5 is arranged between the positive electrode layer 4 and the negative electrode layer 7.

[0087] Next, in step S4, at least one layer selected from the electrode layer and the solid electrolyte layer 5 is heated to the pressing temperature. In this embodiment, for example, when flat plate pressing is used, the assembly can be heated to the pressing temperature by heating the plate in contact with the assembly during pressing. When roller pressing is used, the assembly can also be heated to the pressing temperature by heating the roller.

[0088] Next, in step S5, at least one layer selected from the electrode layer and the solid electrolyte layer 5 is pressed at a pressing temperature. Specifically, the assembly is pressed in a manner that a load is applied in the thickness direction of each layer. At this time, at least one layer selected from the electrode layer and the solid electrolyte layer 5 contains a binder, and the layer containing the binder is pressed at a pressing temperature. In addition, the pressing temperature is higher than the glass transition temperature of the binder. By pressing while heating, the filling rate of the active material and the solid electrolyte is increased, and the contact interface between the particles of the active material and the particles of the solid electrolyte is increased. As a result, the performance of the all-solid-state battery 10 is improved. The "electrode layer" is at least one selected from the positive electrode layer 4 and the negative electrode layer 7.

[0089] Alternatively, the electrode layer and the solid electrolyte layer 5 may be heated to a pressing temperature and pressed separately to form an assembly, and the assembly may be heated and pressed to obtain the all-solid-state battery 10 .

[0090] The pressing temperature is determined by, for example, the surface temperature of the current collector. However, when the heat capacity of the plate or the heat capacity of the roller is sufficiently larger than the heat capacity of the object, the pressing temperature may be, for example, the surface temperature of the plate or the surface temperature of the roller. "Pressing at the pressing temperature" means pressing while maintaining the object at the pressing temperature.

[0091] In the present embodiment, when the assembly is heated to the pressing temperature, the sealing layer 8 is also heated to the pressing temperature. When the assembly is pressed at the pressing temperature, the sealing layer 8 is also pressed at the pressing temperature. Specifically, the entire assembly can be pressed at the pressing temperature in a manner that a load is applied in the thickness direction of each layer. Therefore, the all-solid battery 10 can be easily manufactured. In addition, by heating the sealing layer 8 to the pressing temperature for pressing, the sealing strength brought by the sealing layer 8 is maintained. As a result, the performance of the all-solid battery 10 is improved.

[0092] After the above steps, the all-solid-state battery 10 is obtained.

[0093] When the pressing temperature is lower than the glass transition temperature of the binder, the binder undergoes elastic deformation when the electrode layer and / or the solid electrolyte layer are pressed. If the binder dispersed in the grain boundaries of the particles of the electrode active material and the particles of the solid electrolyte undergoes elastic deformation, part of the load caused by the pressing will cause the electrode layer and / or the solid electrolyte layer to deform in a direction orthogonal to the pressing direction. When the load caused by the pressing is removed, the binder will restore its original shape and original position. As a result, the electrode plate is warped. In the case of a structure with the electrode layer on top and the collector on the bottom, the electrode plate is warped in an upward convex shape. In addition, in the case of a structure with the electrode layer on the bottom and the collector on the top, the electrode plate is warped in a downward convex shape. Since the positive electrode layer is opposite to the negative electrode layer, the positive electrode and the negative electrode are warped in a manner that the positive electrode is close to the negative electrode in the center of the battery and the positive electrode is far away from the negative electrode in the periphery of the battery. Therefore, the distance between the end of the positive electrode collector and the end of the negative electrode collector becomes larger, resulting in a decrease in the sealing strength brought by the sealing layer.

[0094] In addition, when the warpage of the electrode plate is large, cracks may occur between the electrode layer and the current collector, or the electrode layer may be separated from the current collector. In this case, the performance of the battery may be reduced.

[0095] In contrast, in the present embodiment, the pressing temperature is higher than the glass transition temperature of the binder. Therefore, during pressing at the pressing temperature, the binder undergoes plastic deformation. The binder dispersed in the grain boundaries of the particles of the electrode active material and the particles of the solid electrolyte acts by pressing to reduce the gaps between the particles. As a result, the binder undergoes plastic deformation. In other words, the electrode layer stretches in a direction orthogonal to the pressing direction, and the binder undergoes plastic deformation along with this. Therefore, even if the load caused by the pressing is removed, the stretching in the direction orthogonal to the pressing direction will be greatly suppressed. Since the sealing layer 8 is not separated from the end of the positive electrode collector 3 and the end of the negative electrode collector 6, the sealing strength can be maintained.

[0096] When the pressing temperature is higher than the glass transition temperature of the adhesive, the adhesive exhibits plastic deformation behavior. Although the adhesive will also deform in accordance with the deformation direction of the electrode layer caused by the pressing, even if the load caused by the pressing is removed, the stress to restore the original shape will be relieved. In other words, the tensile stress of the electrode layer is relieved. As a result, the warping of the electrode plate is greatly suppressed, so that the sealing strength can be maintained.

[0097] The difference between the pressing temperature and the glass transition temperature of the binder is, for example, 0°C or more and 40°C or less. When the pressing temperature is higher than the glass transition temperature of the binder, the binder can be fully plastically deformed during pressing, thereby suppressing the deformation of the pressed electrode layer and / or solid electrolyte layer 5. In other words, the warping of the electrode plate is suppressed, so it is difficult for the sealing layer 8 to peel off from the collector. Since the sealing strength brought by the sealing layer 8 is fully ensured, an all-solid battery 10 with high mechanical strength can be provided.

[0098] The glass transition temperature of the sealing material is, for example, higher than the glass transition temperature of the adhesive. In this case, the pressing temperature may be higher than the glass transition temperature of the sealing material. When the pressing temperature is higher than the glass transition temperature of the sealing material, the sealing material is plastically deformed by pressing at the pressing temperature. However, when the difference between the glass transition temperature of the sealing material and the glass transition temperature of the adhesive is large, the plastic deformation of the sealing material is more suppressed than the plastic deformation of the adhesive. As a result, the sealing strength brought by the sealing layer 8 is fully ensured, so that an all-solid battery 10 with high mechanical strength can be provided.

[0099] The glass transition temperature of the sealing material may be higher than the pressing temperature. The difference between the glass transition temperature of the sealing material and the pressing temperature is, for example, greater than 0°C and less than 20°C. When the glass transition temperature of the sealing material is higher than the pressing temperature, the shape of the sealing layer 8 is maintained because plastic deformation of the sealing material caused by pressing does not occur. Therefore, in the manufactured all-solid battery 10, the sealing strength brought by the sealing layer 8 is fully ensured, so that an all-solid battery 10 with high mechanical strength can be provided.

[0100] As described above, when the pressing temperature is higher than the glass transition temperature of the binder and lower than the glass transition temperature of the sealing material, the warping of the electrode plate can be suppressed and the sealing strength of the sealing layer 8 can be maintained. Thus, the mechanical strength of the all-solid battery 10 including the sealing layer 8 can be ensured.

[0101] Example

[0102] Hereinafter, the present disclosure will be described in more detail by way of examples. The following examples are merely examples, and the present disclosure is not limited to the following examples.

[0103] (Sample 1)

[0104] A solid electrolyte and a binder are mixed to obtain a mixture. The mixture is attached to a current collector by a coating process. Thus, an electrode plate having a current collector and a solid electrolyte layer is obtained. Styrene ethylene butylene styrene thermoplastic elastomer (Tuftec M1913 manufactured by Asahi Kasei Corporation, glass transition temperature is 90°C) is used as a binder. The produced electrode plate is placed on a metal plate heated to 120°C, heated to a pressing temperature, and pressed at the pressing temperature. The pressing temperature is set to 120°C. The heated metal plate is much thicker than the electrode plate, and the difference in heat capacity is large enough, so the temperature of the metal plate is used as the temperature of the electrode plate. Furthermore, the temperature of the metal plate is measured using a thermocouple arranged inside the plate.

[0105] (Sample 2)

[0106] An electrode plate was obtained in the same manner as in Sample 1 except that the pressing temperature was set to 25° C. (room temperature).

[0107] The photo of the electrode plate after pressing is shown in Figure 3 and 4 middle.

[0108] like Figure 3 As shown, the warping of the electrode plate was suppressed after pressing in the electrode plate of Sample 1. The warping of the electrode plate was suppressed by pressing at a temperature higher than the glass transition temperature of the binder.

[0109] On the other hand, Figure 4 As shown, the electrode plate of Sample 2 was greatly warped after pressing. That is, since pressing was performed at a temperature lower than the glass transition temperature of the binder, the warping of the electrode plate could not be suppressed.

[0110] Industrial Availability

[0111] The technology disclosed in the present invention can be used for batteries of portable information terminals, portable electronic devices, household power storage devices, motorcycles, electric vehicles, hybrid electric vehicles, and the like.

[0112] Description of Reference Numerals

[0113] 3. Positive electrode collector

[0114] 4 Positive electrode layer

[0115] 4t Side view of the positive electrode layer

[0116] 5 Solid electrolyte layer

[0117] 5t Side view of solid electrolyte layer

[0118] 6 Negative electrode collector

[0119] 7 Negative electrode layer

[0120] 7t Side view of negative electrode layer

[0121] 8 Sealing layer

[0122] 10.10B all-solid-state battery

[0123] 11 Positive electrode

[0124] 12 Negative electrode

Claims

1. An all-solid-state battery comprising: Electrode layer; Current collector; a solid electrolyte layer comprising a solid electrolyte; and A sealing layer comprising a sealing material, At least one selected from the electrode layer and the solid electrolyte layer contains a binder, The glass transition temperature of the sealing material is higher than the glass transition temperature of the adhesive, The adhesive comprises a thermoplastic resin, The sealing layer is in contact with the side surface of the solid electrolyte layer and is not in contact with the electrode layer. The thermoplastic resin comprises at least one selected from styrene-butadiene copolymer and styrene-ethylene-butadiene copolymer, The sealing layer is in contact with the current collector, The all-solid-state battery is manufactured through a process of pressing at least one selected from the electrode layer and the solid electrolyte layer at a pressing temperature higher than the glass transition temperature of the binder and lower than the glass transition temperature of the sealing material.

2. The all-solid-state battery according to claim 1, The electrode layer and the solid electrolyte layer are stacked on each other.

3. The all-solid-state battery according to claim 1 or 2, The adhesive has a glass transition temperature below 120°C.

4. The all-solid-state battery according to claim 1 or 2, The sealing material has a glass transition temperature of 120° C. or higher.

5. The all-solid-state battery according to claim 1 or 2, The sealing material includes polyimide.

6. The all-solid-state battery according to claim 1 or 2, The electrode layer includes an electrode active material and the solid electrolyte.

7. A method for manufacturing an all-solid-state battery, comprising: heating at least one selected from the electrode layer and the solid electrolyte layer to a pressing temperature; as well as pressing at least one selected from the electrode layer and the solid electrolyte layer at the pressing temperature, forming a sealing layer in contact with a side surface of the solid electrolyte layer and not in contact with the electrode layer, and forming a current collector in such a manner that the sealing layer is in contact with the current collector, One or both of the electrode layer and the solid electrolyte layer to be pressed at the pressing temperature contains a binder, The pressing temperature is higher than the glass transition temperature of the adhesive, When at least one selected from the electrode layer and the solid electrolyte layer is heated to the pressing temperature, the sealing layer is heated to the pressing temperature, When at least one selected from the electrode layer and the solid electrolyte layer is pressed, the sealing layer is pressed at the pressing temperature.

8. The method for manufacturing an all-solid-state battery according to claim 7, The glass transition temperature of the sealing material constituting the sealing layer is higher than the glass transition temperature of the adhesive.

9. The method for manufacturing an all-solid-state battery according to claim 8, The sealing material constituting the sealing layer has a glass transition temperature higher than the pressing temperature.

Citation Information

Patent Citations

  • Method of manufacturing electrode body, and electrode body

    JP2012038425A

  • Bipolar type lithium ion battery and manufacturing method thereof

    JP2017073374A

  • Process for manufacturing secondary battery

    US20100192364A1

  • Power storage device and electronic device

    US20180233780A1